SUBSIDENCE HISTORY, CRUSTAL STRUCTURE, AND THERMAL EVOLUTION OF THE VALENCIA TROUGH - A YOUNG EXTENSIONAL BASIN IN THE WESTERN MEDITERRANEAN - Watts, A; Torne, M (1992)
The Valencia Trough is an extensional basin that began rifting during the late Oligocene-early Miocene, yet is is located within a region of compression between the European and African plates. Although the trough appears symmetric on bathymetric maps, seismic and gravity and geoid data indicate a fundamental asymmetry in its deep crustal and upper mantle structure. There is good agreement between the predicted depth to the Moho based on a stretching model and the seismically constrained depth beneath the Catalan margin, but poor agreement beneath Mallorca. The seismic Moho beneath Mallorca can be explained by a model in which the crust was modified by the flexural effects of thrust/fold loading. Geoid data suggest that the differences in the crustal structure between the two margins extend into the upper mantle. -from Authors